2003
DOI: 10.1037/0021-843x.112.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Testing Mediational Models With Longitudinal Data: Questions and Tips in the Use of Structural Equation Modeling.

Abstract: R. M. Baron and D. A. Kenny (1986; see record 1987-13085-001) provided clarion conceptual and methodological guidelines for testing mediational models with cross-sectional data. Graduating from cross-sectional to longitudinal designs enables researchers to make more rigorous inferences about the causal relations implied by such models. In this transition, misconceptions and erroneous assumptions are the norm. First, we describe some of the questions that arise (and misconceptions that sometimes emerge) in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
2,952
3
19

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,885 publications
(3,002 citation statements)
references
References 72 publications
28
2,952
3
19
Order By: Relevance
“…Although nonexperimental studies can never prove definitively that the relationship between two variables is a causal one (Cole & Maxwell, 2003;West & Hepworth, 1991); the present results suggest that forgiveness can be added to the list of adaptive psychological processes that are negatively associated with rumination. Using short-term longitudinal methods and a statistical model for depicting forgiveness as a process of psychological change (McCullough et al, 2003), we found that rumination was related inversely to forgiveness in two ways.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although nonexperimental studies can never prove definitively that the relationship between two variables is a causal one (Cole & Maxwell, 2003;West & Hepworth, 1991); the present results suggest that forgiveness can be added to the list of adaptive psychological processes that are negatively associated with rumination. Using short-term longitudinal methods and a statistical model for depicting forgiveness as a process of psychological change (McCullough et al, 2003), we found that rumination was related inversely to forgiveness in two ways.…”
Section: Discussioncontrasting
confidence: 55%
“…In Study 3, we replicated the main findings of Studies 1 and 2 by using data from a 21-day diary study that allowed for an examination of the cross-lagged associations of rumination and forgiveness (Cole & Maxwell, 2003;Finkel, 1995;West & Hepworth, 1991). With these data, we were able to evaluate the possibility that rumination on any given day predicted how much avoidance and revenge motivation one would experience on the following day.…”
Section: Summary Of Studymentioning
confidence: 90%
“…Because peer-rated data were not available in this study, it would be useful to examine the relations of effortful control and resiliency to peer-rated social status in future work. Finally, Cole and Maxwell (2003) suggested that the optimal test of mediation involves at least three time points. Although our test of mediation is considered optimal with only two waves of data, our mediational analyses should be considered as producing results that are merely consistent with the hypothesis that resiliency mediates the relations of effortful control and impulsivity to quality of social functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal designs with data collected at two time points provide the opportunity to examine whether parenting behaviors are predictors of change in child externalizing behaviors from one time point to the next (Cole & Maxwell, 2003;Loeber & Farrington, 1994), and whether the parenting behaviors have specific or diffuse associations with child externalizing versus internalizing outcomes. With more than two data points, it is possible to address not only the specificity of parenting, but also the reciprocity of parenting behaviors and child externalizing behaviors.…”
Section: Methodological Considerationsmentioning
confidence: 99%